Predisposing factors for increased cortisol levels in oral cancer patients - Figueira, Jéssica Araújo [UNESP]; Sarafim-Silva, Bruna Amélia Moreira [UNESP]; Gonçalves, Gislene Maria [UNESP]; Aranha, Laerte Nivaldo; Lopes, Flávia Lombardi [UNESP]; Corrente, José Eduardo [UNESP]; Biasoli, Éder Ricardo [UNESP]; Miyahara, Glauco Issamu [UNESP]; Bernabé, Daniel Galera [UNESP] (Elsevier, 2022)
Cancer patients may have a dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis and abnormal secretion of cortisol. Increased cortisol levels have been associated with worse prognosis in patients with different types of tumors. Although anxiety and depression can trigger an abnormal cortisol secretion, little is known regarding the influence of these emotional disorders on HPA axis dysregulation in cancer patients when evaluating together with demographic, clinicopathological and biobehavioral variables. This cross-sectional study analyzed the pre-treatment plasma cortisol levels of 133 patients with oral squamous cell carcinoma (OSCC) and its association with demographic, clinicopathological, biobehavioral and psychological variables. Plasma cortisol levels were measured by electrochemiluminescence, and anxiety and depression symptoms were assessed using Beck Anxiety Inventory (BAI) and Depression (BDI), respectively. Demographic, clinicopathological and biobehavioral data were collected from patients' medical records. Results from multivariate analysis showed that the occurrence of cancer-induced pain was predictive for higher cortisol levels (OR = 5.388, p = 0.003). Men with OSCC were 4.5 times more likely to have higher plasma cortisol levels than women (OR = 4.472, p = 0.018). The effect of sex on cortisol concentrations was lost in the adjusted model for clinical staging (OR = 2.945, p = 0.116). The absence of chronic alcohol consumption history was a protective factor for highest hormone concentrations in oral cancer patients (OR = 0.104, p = 0.004). Anxiety symptoms measured by BAI as “hands trembling” (OR = 0.192, p = 0.016) and being “nervous” (OR = 0.207, p = 0.0004) were associated with lower cortisol levels. In contrast, the feeling of “fear of losing control” was a risk factor for highest hormone concentrations (OR = 6.508, p = 0.0004). The global score and specific symptoms of depression measured by the BDI were not predictive for plasma hormone levels (p > 0.05). Together, our results show that pain, alcohol consumption and feeling fear are independent factors for increased systemic cortisol levels in patients with oral cancer. Therefore, psychological intervention, as well as control of pain and alcohol consumption, should be considered to prevent the negative effects of cortisol secretion dysregulation in cancer patients.
Keywords: Alcohol; Anxiety; Cancer; Cortisol; Depression; Fear; Head and neck cancer; HPA axis; Oral cancer; Pain; Psychological disorders; Stress